The view from the cheap seats [compact disc, unabridged] : selected nonfiction - Gaiman, Neil (HarperCollins Publishers, 2016)
Presents a collection of nonfiction essays on a myriad of topics--from art and artists to dreams, myths, and memories--observed in the author's distinctive, probing, and amusing style.